Turkic borrowings in the Arabic language of the Mamluk-Kipchak written monuments - Ragıp Мұхаммед; Torebekova Сауле (Turkic Studies Journal, 2022)
The Mamluk state is a country consisting mainly of Kipchaks who ruled Egypt and Syria in the XIII-XVI centuries. Those Kipchak personalities came to power from slaves-Warriors. The word Mamluk in Arabic [malaka] – possession, power; means “white slavers”. These slaves, who were originally in military service, eventually became the main military structure of Egypt and Syria, contributing to the political life of the Muslim states in the region. Thus, it becomes the main force in the military and political system. Although most of the population was Arabs, this state was ruled by the Turks. They spoke their native language and ruled in the Kipchak. In Egypt, the rule of the Mamluk authorities was so strong that the Arabs began to learn the Kipchak language. In order to study the Kipchak language, a bilingual (Arabic-Kipchak) grammar manual and a dictionary-based manuscript have been prepared for this language. These manuscripts are important for studying the history and word stock of the Turkic language, and also methods of teaching the Turkic language. The dictionary section of manuscripts written in the Mamluk-Kipchak language under consideration traditionally shows first Arabic words, and then their equivalents in Turkic languages. In some cases, the head of the Arabic registry is represented by words such as Persian, Turkic, and Aramaic. In the preparation of such manuscripts, not always classical Arabic was used, but also spoken Arabic of that period. In the spoken Arabic language of that era, many words came from different cultures and different languages. In our research article, it was determined that some of the Arabic words at the beginning of the register in Arabic-Kipchak dictionaries written in the Mamluk-Kipchak language are Turkic words of origin, the state of use of these words in Modern Arabic dialects and their place in Arabic culture.